2018
DOI: 10.1371/journal.pntd.0006635
|View full text |Cite
|
Sign up to set email alerts
|

Human plague associated with Tibetan sheep originates in marmots

Abstract: The Qinghai-Tibet plateau is a natural plague focus and is the largest such focus in China. In this area, while Marmota himalayana is the primary host, a total of 18 human plague outbreaks associated with Tibetan sheep (78 cases with 47 deaths) have been reported on the Qinghai-Tibet plateau since 1956. All of the index infectious cases had an exposure history of slaughtering or skinning diseased or dead Tibetan sheep. In this study, we sequenced and compared 38 strains of Yersinia pestis isolated from differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Early evolution: plague in prehistory. The time of divergence between Y. pestis and Y. pseudotuberculosis has been difficult to determine given the wide temporal interval produced by recent molecular dating attempts 92,130,[169][170][171][172][173][187][188][189][190][191][192][193][194][195][196][197][198][199]200 , are shown as grey circles within their geographical country or region of isolation, and the size of each circle is proportional to the number of strains sequenced from each location (number indicated when more than one genome is shown). The areas highlighted in brown are regions that contain active plague foci as determined by contemporary or historical data.…”
Section: Demographic Modelmentioning
confidence: 99%
“…Early evolution: plague in prehistory. The time of divergence between Y. pestis and Y. pseudotuberculosis has been difficult to determine given the wide temporal interval produced by recent molecular dating attempts 92,130,[169][170][171][172][173][187][188][189][190][191][192][193][194][195][196][197][198][199]200 , are shown as grey circles within their geographical country or region of isolation, and the size of each circle is proportional to the number of strains sequenced from each location (number indicated when more than one genome is shown). The areas highlighted in brown are regions that contain active plague foci as determined by contemporary or historical data.…”
Section: Demographic Modelmentioning
confidence: 99%
“…It has been emphasized that for plague to persist and cause human spillovers for centuries a plurality of rodents and fleas, sylvatic and commensal (Dubyanskiy and Yeszhanov 2016 ; Jones et al 2019 ), would have been involved in any given region. That small ruminants and camels can maintain the disease as well could be another important factor (Malek et al 2016 ; Dai et al 2018 ). While repeated reemergences from regional rodent reservoirs may have been associated with climate, not knowing where plague focalised or what species were involved complicates attempts to discern a consistent ‘signal’, such as an unusually wet-humid growing season on the heels of a drought (Ben Ari et al 2011 ), in available paleoclimate proxies.…”
Section: Plagues and Climate In Mediterranean History Some Initial Smentioning
confidence: 99%
“…Primary pneumonic plague is said to be the result of transmission via respiratory droplets from one human to another although the index case in a series may sometimes be the result of handling dead infected animals or companion animals such as cats and dogs. 23 The Plague Commission, operating in the Indian sub-continent in the early twentieth century, found that the vast majority of cases in this theatre, at that time, were of the bubonic type and such cases were not infectious to other humans since relatively few cases progressed to secondary pneumonic plague. 24 On the other hand, the Report of the International Plague Conference of 1911 in Mukden, Manchuria, described an epidemic causing the death of more than 50,000 individuals, which was almost exclusively pneumonic being clearly infectious and not needing the presence of an arthropod vector.…”
Section: The Identity Of the Pathogen Responsible For Historical And mentioning
confidence: 99%